(untitled) (Materiali di Estetica. Terza serie, 2020)
The issue of the nature of happiness or well-being and that of the role that it plays in the meaningful life of people are widely debated today, not only in the theoretical ambit, but also in the empirical one. Most philosophers and psychologists, above all in the Anglophone community, privilege, from this point of view, the traditional paradigms of hedonism or eudemonism. After having expounded my perplexities regarding these models, I present a positive-phenomenological account of happiness. From this perspective, the stratification of the affective life of a person, in conformity with the type of experiences experienced, is respected. In addition, the reciprocity connection between the good quality of a life and the good quality of others’ lives becomes understandable here. Happiness, which a good person “carries on her/his shoulder”, as Scheler says, reveals itself as the feeling through which she/he implicitly experiences her/his own moral value.